Pelatihan Pembuatan Sabun Dari Minyak Jelantah Pada Kader PKK Di Desa Bengkaung - Hanifa, Nisa Isneni; Hidayati, Agriana Rosmalina; Mukhlishah, Neneng Rachmalia Izzatul; Subaidah, Windah Anugrah; Purnomo, Indra; Bayani, Faizul (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The repeated use of cooking oil more than twice is still common in Indonesian society. However, used cooking oil can negatively affect health, being even more detrimental than saturated fatty acids. Additionally, it contributes to pollution in soil and water. One effective method for repurposing used cooking oil is by converting it into soap. This community service initiative aims to promote the utilization of used cooking oil in economically valuable products while reducing the amount of waste oil that is discarded into the environment. The training was conducted for PKK cadres in Bengkaung Village and facilitated by pharmacists, dermatologists, and students from the Faculty of Medicine and Health Sciences at the University of Mataram. The soap-making process begins by adding charcoal to the used cooking oil for 72 hours. This step helps remove hazardous substances and unpleasant odors. Afterward, the oil is filtered and combined with essential soap-making ingredients, including sunflower oil, virgin coconut oil (VCO), olive oil, sodium hydroxide (NaOH), and water. NaOH is critical for the saponification process, which transforms the oil into soap. To enhance the aesthetic value and benefits of the soap, ingredients like honey, yogurt, or natural dyes such as butterfly pea flowers can be incorporated. The mixture is then poured into molds and allowed to harden. Given the simple process and the ease of obtaining the necessary tools and materials, the PKK cadres in Bengkaung Village have shown enthusiasm for making soap from used cooking oil. This activity is expected to broaden their knowledge and provide business opportunities to help increase family income in the village.